2016
DOI: 10.3892/ol.2016.5473
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia regulates CD44 expression via hypoxia-inducible factor-1α in human gastric cancer cells

Abstract: Abstract. Hypoxia induces proliferation and invasion in cancer cells via hypoxia-inducible factor (HIF)-1α. The cell adhesion molecule cluster of differentiation (CD) 44 has been associated with increased cell invasion and metastasis. Whether hypoxia regulates the expression of CD44 in gastric cancer cells remains to be established. In the current study, the effects of hypoxia on HIF-1α and CD44 expression levels in human gastric cell lines SGC-7901 and BGC-823 were evaluated. The cells were cultured in 1% O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
(38 reference statements)
2
26
0
Order By: Relevance
“…In MDA-MB231 breast cancer cells, hypoxia-mediated HIF-1α elevation upregulated CD44 expression, and the co-localization of HRE-driven fluorescence and CD44-positive region was observed in MDA-MB-231 tumors ( Krishnamachary et al ., 2012 ). Exposure of gastric cancer cells to hypoxic conditions led to the elevation in CD44 expression ( Liang et al ., 2017 ). In the current study, we demonstrated that the overexpression of CD44s in non-aggressive breast cancer MCF-7 cells enhanced hypoxia-inducible HIF-1α accumulation, and thereby exhibited higher HRE-luciferase activity and VEGF expression during hypoxia compared to the control MCF-7.…”
Section: Discussionmentioning
confidence: 99%
“…In MDA-MB231 breast cancer cells, hypoxia-mediated HIF-1α elevation upregulated CD44 expression, and the co-localization of HRE-driven fluorescence and CD44-positive region was observed in MDA-MB-231 tumors ( Krishnamachary et al ., 2012 ). Exposure of gastric cancer cells to hypoxic conditions led to the elevation in CD44 expression ( Liang et al ., 2017 ). In the current study, we demonstrated that the overexpression of CD44s in non-aggressive breast cancer MCF-7 cells enhanced hypoxia-inducible HIF-1α accumulation, and thereby exhibited higher HRE-luciferase activity and VEGF expression during hypoxia compared to the control MCF-7.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of HA and CD44 was found to promote epidermal growth factor receptor (EGFR)-mediated pathways in different tumor entities, in turn leading to tumor cell proliferation and survival via mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K)/AKT activation [156]. Within the hypoxic tumor areas CD44 gene expression is induced via hypoxia-inducible factor (HIF)-1α [157]. In agreement with these data, increased CD44 levels were associated with tumor hypoxia in HNSCC patients [27].…”
Section: Clinical Implication Of Hnscc Stem Cellsmentioning
confidence: 99%
“…It has previously been shown that hypoxia potentiated the anabolic effects of HA, including the redifferentiation of articular chondrocytes and synthesis of ECM, through enhancing CD44 expression and binding affinity (Ichimaru et al, 2016). Furthermore, previous research suggested that hypoxia could enhance the expression of CD44 via HIF-1α (Liang et al, 2017). Based on the bioinformatics databases JASPAR (Web ref.…”
mentioning
confidence: 99%